Application of the contextual teaching and learning model assisted by geogebra to enhance eighth-grade students’ mathematical understanding of systems of linear equations in two variables - Sihombing, Karlina; Fitriani, Nelly; Amelia, Risma (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
The purpose of this study is to obtain descriptive results regarding the application of the ctl model assisted by geogebra to improve mathematical understanding before and after the implementation of the ctl teaching approach assisted by geogebra in class viii smpn satap jayakerta for systems of linear equations in two variables material. 10 students were the subjects in this study. experiments in the form of comprehension ability test questions are the methods applied in this study. data analysis was carried out by implementing the pre-experimental design with the one group pretest-posttest design design. the findings in this study indicate that there is an influence of the ctl teaching approach using geogebra, found in the data analysis that has a sign value ≤0.05 which means that there is an increase in mathematical understanding before and after the implementation of the ctl teaching model assisted by geogebra for systems of linear equations in two variables material.